English Teachers’ Feedback on Students’ Writing Work in the New Normal Era: Teachers' Feedback; Writing Skills - Khaerul Fadli; Lalu Ari Irawan; Haerazi Haerazi (Journal of Language and Literature Studies, 2021)
Feedback is information from the teacher to the students regarding to the students’ error in learning process, and the purpose of feedback given by the teacher could improve students’ abilities in learning. In learning writing, feedback from the teacher is needed by the students to improve their writing skills. Writing is a complex process, arranging several words into a sentence and arranging several sentences into a paragraph is not an easy thing to do. In addition, in writing a sentence, the correct words are needed so that the reader can easily understand the intent written by the author. Thus, this study aims to find out what types of feedback given by the teacher to students in this new normal era, and what types of feedback can improve students' writing skills. This research used qualitative descriptive research. For data collection, researcher used the interview notes, study document, and observation. This study took two English teachers and eight students. In this study, the researcher interviewed English teachers and students regarding the feedback the teacher gave during this new normal era. The researcher found that the teachers used two types of feedback i.e. oral and written feedback in correcting students' writing assignments. In addition, the researcher found that all students experienced improvement after they were given feedback by the teacher. Most students’ perception about feedback given by the teachers, oral feedback is very effective and can improve their writing quality.